Changes in roller skiing economy among Nordic combined athletes leading up to the competition season - Yanaka, Takuya; Nakamura, Mariko; Yamanobe, Kaoru; Ishige, Yusuke (Frontiers in Sports and Active Living, 2024)
The purpose of this study was to compare roller skiing economy during different training phases in Nordic combined (NC) athletes and determine the aerobic and anaerobic factors responsible for changes in skiing economy. Seven elite NC athletes underwent incremental load tests on a large buried treadmill in both spring and autumn using roller skis. Measurements included oxygen uptake, respiratory exchange ratio, and blood lactate concentration. Roller skiing economy was calculated from aerobic and anaerobic energy system contributions, and overall roller skiing economy was determined by combining the two. Comparisons were made between the skiing economies obtained in the two measurement sessions. Physical characteristics and incremental test performance remained consistent between the two measurement sessions. The overall skiing economy at each speed significantly improved toward the competition season (p < 0.05). Similarly, the contribution of anaerobic energy system at each speed showed significant improvement (p < 0.05). In contrast, the contribution of aerobic energy system did not change between the two measurement sessions. This study reveals that NC athletes enhance their skiing economy at the same speed during submaximal efforts in preparation for the competition season. This improvement is predominantly associated with an improvement in the contribution of anaerobic energy system.